2012
DOI: 10.1515/hf-2011-0202
|View full text |Cite
|
Sign up to set email alerts
|

Study of thin films of kraft lignin and two DHPs by means of single-molecule force spectroscopy (SMFS)

Abstract: This is a published version of a paper published in Holzforschung.Citation for the published paper: Norgren, M., Notley, S. (2012 AbstractThe adhesion of single and associated lignin chains to a substrate has been studied by means of single-molecule force spectroscopy (SMFS). Softwood kraft lignin (KL) and two lignin polymer models (dehydrogenation polymers, DHPs) based on coniferyl alcohol (DHP c.alc. ) and coniferaldehyde (DHP c.ald. ) were in focus. The desorption force from the " silicon nitride SMFS tip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…As G CHO and G CHOH residues are mostly interlinked with β– O –4 ether linkages in planta ( Yamamoto et al, 2020 ), we designed β– O –4 interlinked homomeric heptamers of G CHO and G CHOH (with or without αC–OH) according to previous characterization studies ( Grabber et al, 1998 ; Jourdes et al, 2007 ; Holmgren et al, 2009 ; Dima et al, 2015 ). Such lignin oligomers composed of only G CHO , G CHOH, or S CHOH have been chemically synthesized in vitro ( Ito et al, 2002 ; Önnerud et al, 2002 ; Holmgren et al, 2009 ; Tobimatsu et al, 2010 ; Notley and Norgren, 2012 ; Koshiba et al, 2013 ; Blaschek et al, 2020a ). Molecular dynamic simulations showed that oligomers of G CHO , which maintain an unsaturation in β– O –4 linkages ( Grabber et al, 1998 ; Jourdes et al, 2007 ; Holmgren et al, 2009 ), greatly reduce the rotation of the α C– β C torsions but not the rotation around β C–O or C 6 –O– α C compared to G CHOH with or without αC–OH ( Supplemental Figure S11, A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…As G CHO and G CHOH residues are mostly interlinked with β– O –4 ether linkages in planta ( Yamamoto et al, 2020 ), we designed β– O –4 interlinked homomeric heptamers of G CHO and G CHOH (with or without αC–OH) according to previous characterization studies ( Grabber et al, 1998 ; Jourdes et al, 2007 ; Holmgren et al, 2009 ; Dima et al, 2015 ). Such lignin oligomers composed of only G CHO , G CHOH, or S CHOH have been chemically synthesized in vitro ( Ito et al, 2002 ; Önnerud et al, 2002 ; Holmgren et al, 2009 ; Tobimatsu et al, 2010 ; Notley and Norgren, 2012 ; Koshiba et al, 2013 ; Blaschek et al, 2020a ). Molecular dynamic simulations showed that oligomers of G CHO , which maintain an unsaturation in β– O –4 linkages ( Grabber et al, 1998 ; Jourdes et al, 2007 ; Holmgren et al, 2009 ), greatly reduce the rotation of the α C– β C torsions but not the rotation around β C–O or C 6 –O– α C compared to G CHOH with or without αC–OH ( Supplemental Figure S11, A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the important steps in the preparation of model film is the coating step. Langmuir–Blodgett deposition ,, and spin coating ,,,,, are among the methods preferred by many groups. However, the existing lignin model films have solely been prepared by dissolving lignin in different volatile solvents, such as tetrahydrofuran (THF), ,, 1,4-dioxane, , and ammonium hydroxide, ,,, resulting in lignin model films that may adequately describe the surface chemistry of lignin dried from a solvent but exhibiting dissimilar functional group orientation and accessibility as compared to CLPs.…”
Section: Introductionmentioning
confidence: 99%
“…Single molecule force spectroscopy (SMFS) has emerged as a powerful tool for the study of the mechanical behavior of individual molecules. It has been used to characterize elasticity, DNA binding modes, cell adhesion, protein unfolding, and colloidal forces . It can also be used to measure the force required to remove an adsorbed molecule from a surface, , which can be useful for label-free biosensing .…”
Section: Introductionmentioning
confidence: 99%